2019
DOI: 10.1016/j.jcmg.2018.05.018
|View full text |Cite|
|
Sign up to set email alerts
|

The Prognostic Value of Diastolic and Systolic Mechanical Left Ventricular Dyssynchrony Among Patients With Coronary Heart Disease

Abstract: Systolic and diastolic left ventricular dyssynchrony, as measured by using GSPECT MPI, were associated with adverse outcomes. Moreover, diastolic dyssynchrony appears to provide incremental predictive value to clinical history, electrical dyssynchrony, and left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Beyond the LVEF, delayed times of contraction and dyssynchrony are important independent signs of LV dysfunction . The assessment of myocardial deformation, such as the strain and strain rate, through the tissue Doppler or global longitudinal strain (GLS) or on gated single‐photon emission computed tomography myocardial perfusion imaging could be alternative methods to classify HF patients . The GLS is measured on the basis of the LV longitudinal shortening in systole, and it is an index of systolic function .…”
Section: Left Ventricular Ejection Fraction Based Classification: Opportunities and Limitationsmentioning
confidence: 99%
“…Beyond the LVEF, delayed times of contraction and dyssynchrony are important independent signs of LV dysfunction . The assessment of myocardial deformation, such as the strain and strain rate, through the tissue Doppler or global longitudinal strain (GLS) or on gated single‐photon emission computed tomography myocardial perfusion imaging could be alternative methods to classify HF patients . The GLS is measured on the basis of the LV longitudinal shortening in systole, and it is an index of systolic function .…”
Section: Left Ventricular Ejection Fraction Based Classification: Opportunities and Limitationsmentioning
confidence: 99%
“…Further, diastolic LVMD was associated with all-cause and cardiovascular mortality independent of LVEF. 16 Finally, the few studies that evaluated the prognostic significance of diastolic LVMD via GSPECT MPI suggested a greater value of diastolic over systolic LVMD in selecting CRT candidates among HF patients. 17 The analysis by Alexanderson-Rosas et al assessed the utility of diastolic LVMD measured by GSPECT MPI in patients with HFrEF who underwent CRT.…”
mentioning
confidence: 99%
“…To date, the pathophysiology and clinical value of diastolic LVMD had not been studied extensively. Similar to systolic LVMD, diastolic LVMD could assess the phase and amplitude of regional myocardial relaxation by multiple Fourier transforms to quantify myocardial discoordination in diastole ( 23) and appears to provide incremental value in the prediction of adverse outcomes (28). In our study, both systolic and diastolic LVMD were included and it was suggested that diastolic LVMD was more strongly associated with myocardial viability, as seen in the diastolic phase histogram.…”
Section: Discussionmentioning
confidence: 92%